To Arouse Students' Interest in National Music by Informing them about Shashmaqom Branches - Mamirova Odinahon Karimjon qizi (Research Parks Publishing LLC, 2021)
Shashmaqom is a collection of melodies and songs sung in 6 different scenes and in 6 different moods. Although there are 6 different types of shashmaqom, there are other melodies that are close to it. This status is evident in the songs of the branches. In them, the structure of the frog varies relative to the main branch to which it belongs. The aim of the article is to arouse students' interest in national music by informing them about Shashmaqom branches.